Bariatric surgery in individuals with liver cirrhosis: A narrative review - Cazzo,Everton (2017)
Summary Introduction: Bariatric surgery has become the gold standard treatment for morbid obesity, but there is no consensus regarding its safety and efficacy among individuals with chronic liver diseases. Objective: To critically evaluate the existing evidence on literature about bariatric surgery in individuals with liver cirrhosis. Method: Narrative review performed by means of an online search in the MEDLINE and LILACS databases. Results: Bariatric surgery is safe and effective in individuals with chronic liver disease without clinical decompensation or significant portal hypertension. Individuals with severe liver function impairment present significantly higher surgical morbidity and mortality. Among candidates to liver transplantation, surgery may be performed before, after and even during transplantation, and there is a predominant trend to perform it after. Vertical sleeve gastrectomy seems to be the most adequate technique in this group of subjects. Conclusion: Bariatric surgery is safe and effective in individuals with compensated cirrhosis without significant portal hypertension, but presents higher morbidity. Among candidates to liver transplantation and/or individuals with severe portal hypertension, morbidity and mortality are significantly higher.